UPAYA MENINGKATKAN HASIL BELAJAR SISWA MATERI BANGUN DATAR DENGAN MODEL PROBLEM BASED LEARNING PADA KELAS IV SDN NO 106193 BAKARAN BATU - Saoda (PGSD UMN Al-Washliyah, 2022)
This research was motivated by the results of observations at SDN No. 106193 Bakaran Batu, which was previously known to have low student learning outcomes in mathematics subjects with flat shapes. With this background, the researcher will conduct research with the aim of improving student learning outcomes with the Problem Based Learning model. This research was conducted on fourth grade students of SDN No. 106193 Bakaran Batu with a total of 20 students. This research uses classroom action research (CAR). To complete the research data using instruments consisting of observation sheets and student tests. This research was conducted in two cycles. Each cycle consists of stages of planning, implementation, observation, and reflection. From the results of the research that has been carried out, it shows that this research using the Problem Based Learning model can improve student learning outcomes. The application of the Problem Based Learning model also makes students more active in critical thinking and able to find their own information in solving problems. Prior to the application of the Problem Based Learning learning model, researchers also used (pretest) before learning. From the results of these studies, it can be concluded that in the first cycle, the average student learning outcomes obtained a score of 68 with a completeness percentage of 65%. While in the second cycle the average acquisition of student learning outcomes reached a value of 83.25 with a 90% completeness percentage. Therefore, it can be said that the application of the Problem Based Learning learning model is able to improve student learning outcomes in mathematics subjects in class IV SDN No. 106193 Bakaran Batu.